Mental and physical health outcomes of burnout in athletes: a systematic review and meta-analysis - Glandorf, H. L.; Madigan, D. J.; Kavanagh, O.; Mallinson-Howard, S. H. (International Review of Sport and Exercise Psychology, 2025)
Burnout is a mental health problem that appears to be increasingly common among athletes. Importantly, burnout may also simultaneously increase the risk for other health consequences. In order to examine this idea further, in the present study we provide the first systematic review and meta-analysis of the association between athlete burnout and mental and physical health outcomes. A literature search returned 54 studies (N = 13,976 athletes) examining various negative (e.g. depression, anxiety, insomnia; 27 studies) and positive (e.g. satisfaction, vitality, quality of life; 19 studies) mental health outcomes and physical health outcomes (e.g. biomarkers, somatic symptoms, physiological indices; 18 studies). A systematic review of this literature showed that athlete burnout was associated with both increases in negative mental health outcomes and decreases in positive mental health outcomes. However, evidence for an association between athlete burnout and physical health outcomes was mixed. This broad pattern of findings was supported by a meta-analysis. Our review suggests that burnout may indeed have many negative implications for athletes` health. The findings also identify a need for further research in this area, especially in relation to burnout and its longitudinal association with biomarkers and physiological indices.